2020
DOI: 10.1111/apt.16016
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors of mortality and disease progression among patients with non‐alcoholic fatty liver disease

Abstract: SummaryBackgroundFactors associated with mortality and disease progression in non‐alcoholic fatty liver disease (NAFLD) and non‐alcoholic steatohepatitis (NASH) are poorly understood.AimsTo assess the impact of liver disease severity, demographics and comorbidities on all‐cause mortality and liver disease progression in a large, real‐world cohort of NAFLD patients.MethodsClaims data from the German Institut für angewandte Gesundheitsforschung database between 2011 and 2016 were analyzed retrospectively. Adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 38 publications
0
39
0
6
Order By: Relevance
“…Given the limitations of this method and the very low proportion of patients, who actually undergo liver biopsy, it is no surprise that NAFLD and in particular asymptomatic progressive liver disease (i.e. NASH with compensated cirrhosis) remain severely underdiagnosed 7 . As elevations of serum liver enzyme concentrations are still the most common symptom resulting in further clinical workup and referral to hepatologists 20,21 , in the present study utility of serum liver enzymes for detection or diagnosis of NAFLD or NASH was tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the limitations of this method and the very low proportion of patients, who actually undergo liver biopsy, it is no surprise that NAFLD and in particular asymptomatic progressive liver disease (i.e. NASH with compensated cirrhosis) remain severely underdiagnosed 7 . As elevations of serum liver enzyme concentrations are still the most common symptom resulting in further clinical workup and referral to hepatologists 20,21 , in the present study utility of serum liver enzymes for detection or diagnosis of NAFLD or NASH was tested.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, NAFLD is the hepatic manifestation of the metabolic syndrome and can therefore be a part of the risk strati cation for cardiovascular diseases and other conditions associated to the metabolic syndrome 4,5 . Secondly, Nonalcoholic steatohepatitis (NASH), the progressive form of NAFLD with in ammation and ballooning of hepatocytes in the liver is associated with substantial risk of morbidity and mortality [6][7][8] . It is debatable if NAFL (liver steatosis without relevant in ammation) and NASH have similar risk for cardiovascular and other metabolic comorbidities and both develop signi cant brosis [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…In einer späteren Untersuchung innerhalb der SHIP-Studie wurde für die Jahre 2008-2012 eine Fettleberprävalenz von 42,2 % ermittelt, wobei die Diagnose mittels Magnetresonanztomografie gestellt wurde [16]. Eine aktuelle Studie zur Mortalität von Personen mit einer Fettlebererkrankung hat auf der Basis von Routinedaten der Jahre 2011-2016 eine Prävalenz von 4,7 % ermittelt [17]. Die vorliegende Analyse nutzt ebenfalls Routinedaten und nimmt eine detaillierte Stratifizierung nach Geschlecht oder Alter vor.…”
Section: Hintergrundunclassified
“…Die Inzidenzen im Jahr 2013 (2008) belaufen sich auf 0,83 % (0,81 %) für eine Fettlebererkrankung und auf 0,02 % (0,01 %) für die Fettleberentzündung. Verglichen mit Studien, die eine Stichprobe aus der Allgemeinbevölkerung mittels diagnostischer Verfahren untersucht haben, erscheinen die Ergebnisse zur Diagnosehäufigkeit aus dieser Studie eher gering, decken sich jedoch weitestgehend mit den Ergeb-nissen einer anderen Studie, die ebenfalls Routinedaten verwendet und eine Prävalenz der NAFLD von 4,7 % für die Jahre 2011-2016 ermittelt hat [17]. Während für Europa eine Prävalenz von 24 % angenommen wird [2], zeigen deutsche Daten aus Mecklenburg-Vorpommern eine Prävalenz von 29,9 % auf der Basis einer sonografischen Untersuchung für den Zeitraum 1997-2001 [15] sowie eine Erkrankungsprävalenz, ermittelt über eine Magnetresonanztomografie, von 39,5 % für die Jahre 2008-2013 [16].…”
Section: äNderungen Im Zeitverlaufunclassified
“…Canbay et al 1 recently reported on the patterns and predictors of mortality and disease progression among patients with non‐alcoholic fatty liver disease (NAFLD) in Germany. They concluded that the probability of all‐cause mortality consistently increased with NAFLD progression during a five‐year follow‐up with a substantial increase in the first year after the first diagnosis of NAFLD, cirrhosis, and hepatocellular carcinoma.…”
mentioning
confidence: 99%